1985
DOI: 10.1104/pp.79.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Leaf K+ Interaction with Water Stress Inhibition of Nonstomatal-Controlled Photosynthesis

Abstract: The relationship between leaf K' concentration, in vitro dehydration, and nonstomatal-controlled photosynthesis was investigated using leaf slices that were vacuum infiltrated with media containing varying sorbitol concentrations. Ammonium ions, which facilitate stromal alkalinization, reversed the increased sensitivity of KV-deficient leaf slice photosynthesis to cell dehydration. However, NH4+ had no effect on photosynthesis of K+-deficient leaf slices under nonhypertonic conditions. These data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Photosynthetic rates decreased with the first decrease in water potential, and at -3.11 MPa rates had decreased by 35% from the highest rate at 0 MPa. Berkowitz and Whalen (5) found that photosynthesis of leaf slices from spinach depleted of K4 was more susceptible to dehydration than control plants, similar to the results with wheat found here. The 2 mM K+-grown wheat was also sensitive to dehydration, although less so than the 0.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Photosynthetic rates decreased with the first decrease in water potential, and at -3.11 MPa rates had decreased by 35% from the highest rate at 0 MPa. Berkowitz and Whalen (5) found that photosynthesis of leaf slices from spinach depleted of K4 was more susceptible to dehydration than control plants, similar to the results with wheat found here. The 2 mM K+-grown wheat was also sensitive to dehydration, although less so than the 0.…”
supporting
confidence: 80%
“…These data suggest that suboptimal pH of the stroma during water stress was inhibiting photosynthesis. Last, the K4 protective effect appears to be extrachloroplastic, since chloroplasts isolated from control and K+-deficient plants were inhibited to the same extent by decreased '.. of the assay solution (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in this laboratory (6,17) (6,17), they found no effect of altered K+ status on C02-and light-saturated photosynthesis. However, Rao et al indicated that due to variability in the leaf K+ content in their experiments, they could not completely rule out a role of K+ in alleviating stress effects on chloroplasts.…”
mentioning
confidence: 99%
“…In addition, under water stress, amongst others types of stress, there is a greater reactive oxygen species production (HASEGAWA et al, 2000), which increases the demand for K and induces its high accumulation in plant tissues (BERKOWITZ;CHRISTA, 1985). Adequate amounts of K reduces NADPH oxidase activity, which represents the second major source for ROS production, and protect chloroplasts as ROS production is restricted (CAKMAK, 2005).…”
Section: Introductionmentioning
confidence: 99%